Looking Forward from the Past: Assessing the Potential Flood Hazard and Damage in Polesine Region by Revisiting the 1950 Flood Event - Mattia Amadio; Jaroslav Mysiak; Silvano Pecora; Alberto Agnetti (Fondazione Eni Enrico Mattei (FEEM), 2013)
River floods are a common natural hazard in Europe, causing high mortality and immense economic damage (EM-DAT 2009). Human-induced climate change will alter intensity and frequency of extreme weather events, hence flood risk (IPCC 2012). While large-scale assessments of flood risk dominate (Genovese, et al. 2007), the knowledge of the effects at smaller scales is poor or incomplete, with few localized studies. The approach of this study starts from the definition of the risk paradigm and the elaboration of local climatic scenarios to track a methodology aimed at elaborating and combining the three elements concurring to the determination of risk: hydrological hazard, value exposure and vulnerability. First, hydrological hazard scenarios are provided by hydrological and hydrodynamic models, included in a flood forecasting system capable to define “what-if” scenario in a flexible way. These results are then integrated with land-use data (exposure) and depth-damage functions (vulnerability) in a GIS environment, to assess the final risk value (potential flood damage) and visualize it in form of risk maps. In this paper, results from a pilot study in the Polesine area (Po river basin) are presented, where four simulated levee breach scenarios are compared. This technique is of great interest to decision makers who are interested in gaining knowledge about possible direct losses from river flooding events. It can also be an important tool to guide decision making and planning processes, to help them understand how to reduce risk to river flood events. As future perspective, the employed methodology can also be extended at the basin scale through integration with the existent flood warning system to gain a real-time estimate of floods direct costs.
Keywords: Q25; Q54; 330; Flood Risk/Damage Assessment; Hydrological-Hydrodynamic Modelling; Climate Scenarios; Historical Flood Reassessment; Po River Basin District; Polesine Region (Rovigo Province)